RFI monitoring for the MeerKAT Radio Telescope - Schollar, Christopher (Department of Computer Science, 2016)
South Africa is currently building MeerKAT, a 64 dish radio telescope array, as a pre-cursor for the proposed Square Kilometre Array (SKA). Both telescopes will be located at a remote site in the Karoo with a low level of Radio Frequency Interference (RFI). It is important to maintain a low level of RFI to ensure that MeerKAT has an unobstructed view of the universe across its bandwidth. The only way to effectively manage the environment is with a record of RFI around the telescope. The RFI management team on the MeerKAT site has multiple tools for monitoring RFI. There is a 7 dish radio telescope array called KAT7 which is used for bi-weekly RFI scans on the horizon. The team has two RFI trailers which provide a mobile spectrum and transient measurement system. They also have commercial handheld spectrum analysers. Most of these tools are only used sporadically during RFI measurement campaigns. None of the tools provided a continuous record of the environment and none of them perform automatic RFI detection. Here we design and implement an automatic, continuous RFI monitoring solution for MeerKAT. The monitor consists of an auxiliary antenna on site which continuously captures and stores radio spectra. The statistics of the spectra describe the radio frequency environment and identify potential RFI sources. All of the stored RFI data is accessible over the web. Users can view the data using interactive visualisations or download the raw data. The monitor thus provides a continuous record of the RF environment, automatically detects RFI and makes this information easily accessible. This RFI monitor functioned successfully for over a year with minimal human intervention. The monitor assisted RFI management on site during RFI campaigns. The data has proved to be accurate, the RFI detection algorithm shown to be effective and the web visualisations have been tested by MeerKAT engineers and astronomers and proven to be useful. The monitor represents a clear improvement over previous monitoring solutions used by MeerKAT and is an effective site management tool.